Legal Liability of Illegal Online Loans in the Perspective of Criminal Law - Vanti Y. Rolobessy; Faissal Malik; Suwarti Suwarti (Journal of Social Science, 2023)
This study aims to analyze law enforcement of misuse of personal data related to illegal online loans (fintech) as a form of mayantara crime in a cyber perspective and examine the liability of illegal online loans (illegal fintech desk collectors) in a criminal law perspective. The research method used in this study is the type of research used in the research is normative legal research as a process to find the rule of law, legal principles, and legal doctrines to answer the legal issues faced. The scientific logic that in normative legal research is built on scientific discipline and the ways in which normative legal science works, that is, legal science whose object is law itself. The results of this study show that the enforcement of the Law on Misuse of Personal Data Related to Online Loans (Illegal Fintech) as a Form of Mayantara Crime in a Cyber Perspective is based on the reason that the rampant public activities on electronic media, the Electronic Transaction Information Law was born, namely Law Number 19 of 2016 on Law Number 11 of 2008 concerning Electronic Information and Transactions concerning Electronic Information and Transactions ( ITE) with Considerations can be found in the consideration section, especially in the "Considering" section which states that information globalization has placed Indonesia as part of the world information society so that it requires the establishment of regulations regarding the management of Information and Electronic Transactions at the national level so that the development of Information Technology can be carried out optimally, evenly, and spread to all levels of society in order to educate the nation's life.